Linear Identification of 8 or More Plasma Cells (PCs) in the Interfoveolar Areas (IFAs) of Sleeve Gastrectomies Is Highly Predictive ofHelicobacter pylori (H. pylori) Infection. (9th November 2022) - Akrmah, M; Ibrahim, E; Ligato, S
Abstract: Introduction/Objective: Bariatric surgery for morbid obesity is dramatically increasing, and large number of sleeve gastrectomies is examined histopathologically. The GIPS guidelines recommend using a visual gestalt to identify substantial inflammation for prompting further ancillary testing for H. pylori microorganisms, and a recent study proposed an "Objective Visual Analog Scale" that justifies additional work-up for H. Pylori infection in gastric biopsies. Our study aims to establish a potential correlation between the number of plasma cells in the IFAs and the presence of H. pylori infection in sleeve gastrectomy specimens. Methods/Case Report: We retrospectively reviewed 338 patients who underwent sleeve gastrectomy for morbid obesity at our institution from 2016-2021. Only 105 of 338 cases were included which demonstrated mild to marked lymphoplasmacytic infiltrate in the IFAs of the lamina propria on H&E stain. The number of plasma cells identified in the more expanded IFAs of the lamina propria was assessed by "drawing an imaginary horizontal line" and the number of plasma cells under the "line" were counted. H. pylori immunostain was performed in all cases. Statistical analyses were performed using IBM SPSS statistics Version 26. Results (if a Case Study enter NA): H. pylori like organisms were identified in 49 of 105 cases (20 cases on H&E stain and 29 cases on H. pylori immunostain). Receiver operator characteristic curve (ROC) showed that the identification of 8 or more plasma cells in expanded IFAs is both highly sensitive (93.9%; 46/49) and specific (83.9%; 47/56) for predicting H. Pylori infection with a positive predictive value of 83.6% (46/55) and area under the curve (AUC) of 0.94 (CI:0.89-0.99, p-value= 0.00). Conclusion: In the light of above results, we propose that in sleeve gastrectomies specimens, in which H. pylori is not identified on H&E sections, the linear identification of 8 or more plasma in the more expanded IFAs is highly predictive of H. pylori infection and justify additional workup for H. pylori infection.